PENGARUH PENDIDIKAN KESEHATAN TENTANG DISMENORE TERHADAP SIKAP REMAJA PUTRI DALAM MENANGANI DISMENORE - Arlin Dewi Utari; Yanita Trisetiyaningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Adolescence showed maturation of the reproductive organs one of menstruation. When menstruation dysmenorrhea usually accompanied to disrupt the activities of youth and reduce quality of life of individuals. In Indonesia the incidence of dysmenorrhea amounted to 64.25%. Teens knowledge about dysmenorrhea showed 78.3% of young women are included in the category level of knowledge is lacking. Hence the need for health education about dysmenorrhea, the importance of knowledge about adolescent dysmenorrhea can change attitudes in dealing with dysmenorrhea appropriately and well, so as to achieve healthy behaviors (health behavior). Objective: To determine the effect of health education on the attitudes of young women in dealing with dysmenorrhea. Method: The research design uses methods quasy Experiment pretest and posttest design with non-equivalent control group. The samples used were 36 respondents. Analysis of the data used is univariable and Paried bivariable analysis using t-test and Independent t-test with a significance level of p <0.05. Result: There are differences in the attitude between pretest and posttest in the intervention group with a p-value of 0.000 (<0.05). There are differences in the attitude pretest and posttest control group with a p-value of p-value 0.028 (<0.05). There are differences in the attitude posttest between the intervention group and the control group with a p-value 0.003 (<0.05). Conclusion: There is effect on dysmenorrhea health education on attitudes of young women in dealing with dysmenorrhea in SMP N 1 Pleret. Keyword : Dysmenorhea, Attitude.